IRAS 18153-1651: an H ii region with a possible wind bubble blown by a young main-sequence B star - Gvaramadze, Vasilii V.; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2016)
We report the results of spectroscopic observations and numerical modelling of the H ii region IRAS 18153−1651. Our study was motivated by the discovery of an optical arc and two main-sequence stars of spectral type B1 and B3 near the centre of IRAS 18153−1651. We interpret the arc as the edge of the wind bubble (blown by the B1 star), whose brightness is enhanced by the interaction with a photoevaporation flow from a nearby molecular cloud. This interpretation implies that we deal with a unique case of a young massive star (the most massive member of a recently formed low-mass star cluster) caught just tens of thousands of years after its stellar wind has begun to blow a bubble into the surrounding dense medium. Our 2D, radiation-hydrodynamics simulations of the wind bubble and the H ii region around the B1 star provide a reasonable match to observations, both in terms of morphology and absolute brightness of the optical and mid-infrared emission, and verify the young age of IRAS 18153−1651. Taken together our results strongly suggest that we have revealed the first example of a wind bubble blown by a main-sequence B star.